2016
DOI: 10.1080/00016489.2016.1193893
|View full text |Cite
|
Sign up to set email alerts
|

Association of the recurrence and canceration rate of vocal leukoplakia with interleukin-10 promoter variants over a 2-year period

Abstract: Conclusion This study indicates that IL-10 promoter polymorphism variants, smoking, and alcohol consumption increase the risk of recurrence and canceration in vocal leukoplakia. Objective This prospective, clinical trial was performed to evaluate the association of interleukin (IL)-10 promoter polymorphism variants and canceration and recurrence rates in vocal leukoplakia (a pre-cancerous laryngeal carcinoma lesion) over a 2-year period. Participants and method Sixty-one post-operative patients with vocal leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…Moreover, IL‐10 suppression of antigen presenting cell function in macrophages is dependent on expression of the hematopoietic cell–restricted E3 ubiquitin ligase March I, whereas in DCs, suppression is March I independent 40 . Zhou et al 41 found that there was a significantly higher cancerization rate in the IL‐10 promoter genetic variants group than in the normal genotype group after 2‐year follow‐up of post‐CO 2 laser resection surgery under microlaryngoscopy. However, IL‐10’s role in tumorigenesis and development is still controversial as there is evidence suggesting that IL‐10 has potent antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, IL‐10 suppression of antigen presenting cell function in macrophages is dependent on expression of the hematopoietic cell–restricted E3 ubiquitin ligase March I, whereas in DCs, suppression is March I independent 40 . Zhou et al 41 found that there was a significantly higher cancerization rate in the IL‐10 promoter genetic variants group than in the normal genotype group after 2‐year follow‐up of post‐CO 2 laser resection surgery under microlaryngoscopy. However, IL‐10’s role in tumorigenesis and development is still controversial as there is evidence suggesting that IL‐10 has potent antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…The second difference is noted in the analysis methods. For clinical prognostic studies, we consider binary classification model and its threshold (receiver operating curve analysis), 25 Pearson and Fisher exact χ 2 tests, 22,29,41,44,45,47,49 and Cox proportional hazards model (Kaplan‐Meier method) 28,30,37,38,46,48 more appropriate for yielding applicable data than 1‐way analysis of variance only 32 , 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported risk factors for recurrent VFL include alcohol consumption, smoking, gastroesophageal reflux, the site and size of the lesion, and the pathological grade of the initial lesion. [7][8][9][10] However, there are discrepancies in the literature regarding certain factors, specifically smoking and alcohol consumption, being associated with higher rates of recurrence. [7][8][9][10] Moreover, the recurrence risks associated with the pathological grade and site and size of the lesion remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] However, there are discrepancies in the literature regarding certain factors, specifically smoking and alcohol consumption, being associated with higher rates of recurrence. [7][8][9][10] Moreover, the recurrence risks associated with the pathological grade and site and size of the lesion remain controversial. 4,7,[9][10][11] The risk of recurrence with lesions on the inferior surface of the vocal fold has not been examined.…”
Section: Introductionmentioning
confidence: 99%